Pengaruh Rasio MOCAF dan Tepung Porang Terhadap Mutu Kimia dan Organoleptik Nugget Ikan Tenggiri - Rasyda, Riezka Zuhriatika; Zainuri, Zainuri; Werdiningsih, Wiharyani (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Spanish mackerel (Scomberomorus commerson) nuggets are processed products from highly nutritious mackerel fish, with additional fillers, binders, and seasonings. The type and concentration of fillers and binders could influence the quality of spanish mackerel nuggets. The aim of this study was to determine the best ratio of MOCAF and porang flour that can produce spanish mackerel nuggets that meet SNI 7758:2013 requirements and are liked by panelists. The experimental design used in this study was a Completely Randomized Design consisting of 1 factor (ratio of MOCAF and porang flour) with five treatment levels, namely P1 (30%: 0%), P2 (29.5%: 0.5%), P3 (29%: 1%), P4 (28.5%: 1.5%) and P5 (28%: 2%), and replicated four times. The parameters observed were moisture content, ash content, protein content and organoleptic (hedonic color, aroma, taste, and texture). The data obtained were analyzed at a 5% significant level by analysis of variance (ANOVA) and further tested using the Duncan Test for significantly different effects. The results showed that MOCAF and porang flour ratio significantly affected the moisture content and texture hedonic, but did not affect the ash content, protein content, color hedonics, aroma hedonics, and taste hedonics of spanish mackerel nugget. Moisture content, ash content, and protein content of all treatments have met SNI 7758:2013 requirements. The treatment with MOCAF and porang flour ratio of 28.5%:1.5% with 52.91% (ww) moisture content, 1.26% (ww) ash content and 15.28% (ww) protein content produced spanish mackerel nuggets that were most favored by panelists, thus concluded as the best treatment.